Recognition and recall of vehicles and manufacturer symbols: implications for eyewitness vehicle identifications - Allison, Meredith (Applied psychology in criminal justice, 2014)
The purpose of this study was to examine people's recall and recognition of cars because some witnesses to crimes may see only the getaway car. We compared participants' accuracy in identifying vehicles and manufacturer symbols in a free recall versus recognition questionnaire format. Participants in the recognition condition were more accurate than those in the free recall condition on many of the questions. Across conditions, participants had the most difficulty in remembering the Mazda 3-Series Truck symbol and the Buick and Subaru symbols. The majority of participants were accurate at identifying the Jeep Grand Cherokee and the Honda symbols, and participants with more driving experience were more accurate on some of the questions. Men were more accurate than women on several of the vehicle questions, but on only one manufacturer symbol question. We discuss future eyewitness research and the implications of this study.